A computational approach for investigating the mutational landscape of RAC-alpha serine/threonine-protein kinase (AKT1) and screening inhibitors against the oncogenic E17K mutation causing breast cancer. (December 2019) - Thirumal Kumar, D.; Jain, Nikita; Evangeline, Judith; Kamaraj, Balu; Siva, R.; Zayed, Hatem; George Priya Doss, C.
Abstract: Breast cancer (BC) is the most commonly diagnosed cancer among females worldwide, and among the BC-associated mutations in various proteins, mutations in the RAC-alpha serine/threonine-protein kinase (AKT1) remain the most dominant. We thus attempted to understand the potential molecular pathogenicity profile of the mutations in AKT1 using a comprehensive computational protocol involving analyses of biochemistry-disruption and destabilizing properties and conservation. Our predictions revealed that E17K, R67W, V164G, E319G, R391G, D32Y, L52H, L52R, and W80R were the most pathogenic mutations. In addition, the change of glutamate to lysine at position 17 of AKT1 (E17K) was found to be highly predominant. An extensive two-step molecular dynamics (simple and complex) simulation (MDS) using GROMACS (GROningen MAchine for Chemical Simulations) was then initiated to analyze and understand the structural impact of the E17K mutation on the function of AKT1. The simple MDS analysis revealed that the E17K mutation decreases the compactness and intramolecular hydrogen bonds of the protein. We also performed a virtual screening analysis with 19 AKT inhibitors obtained from the Selleck Chemicals website those satisfied the Lipinski rule of 5. Among these 19 compounds, Akti-1/2 exhibited the best binding affinity with both native AKT1 and the E17K mutant. The molecular interaction study also revealed that the co-crystallized AKT1 inhibitor N-(4-(5-(3-acetamidophenyl)-2-(2-aminopyridin-3-yl)-3H-imidazo [4, 5-b]pyridin-3-yl)benzyl)-3-fluorobenzamide (12j) exhibited a better interaction with native AKT1 compared with the E17K mutant AKT1 protein, whereas, Akti-1/2 exhibited the opposite effects, i.e., a better interaction with the E17K mutant AKT1 than the native AKT1. These findings from the interaction analysis were further supported by the complex MDS, which measured the compactness and intermolecular hydrogen bonds of the proteins. The results obtained in this study suggest that Akti-1/2 might be a better inhibitor for the treatment of BC caused by the E17K mutation in AKT1. Highlights: Structural impact of the E17K mutation. Virtual screening analysis. Akti-1/2 could be a better inhibitor to treat BC.